2021
DOI: 10.3390/ijerph18115561
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Resources and 24,910 Deaths Due to Traffic Accidents: An Ecological Mortality Study in Poland

Abstract: Background: Deaths due to traffic accidents are preventable and the access to health care is an important determinant of traffic accident case fatality. This study aimed to assess the relation between mortality due to traffic accidents and health care resources (HCR), at the population level, in 66 sub-regions of Poland. Methods: An area-based HCR index was delivered from the rates of physicians, nurses, and hospital beds. Associations between mortality from traffic accidents and the HCR index were tested usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Regarding the differences in traffic accident mortality rates between men and women, men exhibit higher rates (4 to 6 times more), as found in studies across Latin America and globally [15][16][17], as well as in our study. The most impacted age group was those over 60 years, paralleling findings in Colombia where patients in this age range faced double the mortality risk from traffic accident compared to younger patients [18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the differences in traffic accident mortality rates between men and women, men exhibit higher rates (4 to 6 times more), as found in studies across Latin America and globally [15][16][17], as well as in our study. The most impacted age group was those over 60 years, paralleling findings in Colombia where patients in this age range faced double the mortality risk from traffic accident compared to younger patients [18].…”
Section: Discussionsupporting
confidence: 89%
“…The 17 to 24-year age group ranked second in mortality rates, mirroring patterns in Argentina, Brazil, Chile in Latin America, and Poland in Europe, where this age group is most affected, attributed to riskier behaviors like speeding and helmet non-use [16,[20][21][22][23]. Our findings indicate a general mortality rate reduction in traffic accident of 1.23%, notably in the sierra, coast, and Amazon regions, in contrast to Brazil, Paraguay, Pakistan, Mongolia, and North Korea, where trends are stable or increasing [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Our study looked further into the distribution of available hospital resources and found that they were not balanced in accordance with mortality rates from RTIs in each province. A paper from Poland reported that poor HCRs were responsible for anomalies in mortality rates due to traffic accidents in each region 9 and that ORs were found to be the least equally distributed out of all the hospital resources. This is due to the extensive process required to provide appropriate venues, as well as surgical teams and equipment, making it harder to open ORs.…”
Section: Overall M (%) C (%) P (%) T (%) B (%) Overall M (%) C (%) P ...mentioning
confidence: 99%
“…A set of different statistical analysis methods has been applied in efforts to determine the correlation between categorical variables over accident datasets. For example, Negative Binomial regression (Msengwa and Ngari, 2021;Mustefa and Belayhun, 2019;Wang et al, 2021;Zou et al, 2021) and Poisson regression (Genowska et al, 2021;Khan and Hussain, 2021;Msengwa and Ngari, 2021;Sagamiko and Mbare, 2021;Twenefour et al, 2021;Wang et al, 2021;Yang et al, 2021), have been widely used to model of count accident dataset to verify the impact of independent variables 𝑋 on the given dependent variables 𝑌. The main difference between Poisson and Negative Binomial when the later releases the restricted hypothesis and the mean value is equal to the variance that made by the Poisson model (Maxwell et al, 2018).…”
Section: Review Of Some Statistical Approaches Of Accident Modelingmentioning
confidence: 99%